Electrochemical Oxidation of Alizarin Red-S on Glassy Carbon Electrode: Mechanistic Study, Surface Adsorption and Preferential Surface Orientation. Issue 7 (21st April 2016) - Dadpou, Bita; Nematollahi, Davood
Abstract : The electrochemical oxidation of alizarin red-S has been studied using cyclic and differential pulse voltammetry, double step chronocoulometry and impedance spectroscopy in aqueous solution on glassy carbon electrode. The results revealed that alizarin red-S shows one oxidation peak and two reduction peaks. Electrochemical adsorption of alizarin red S was also studied in more details on glassy carbon surface. Double layer charge was calculated by chronocoulometric measurement in two ways, by using organic solvent for diminishing surface adsorption and by using a blank solution without alizarin red S. Obtained results showed that alizarin red-S adsorbed on glassy carbon in multi-layer arrays. Computational calculations were done by Chem Bio 3D software and Gaussian software on B3 LYP/6-311 ++ (d, p) level of theory.